DECISION SUPPORT SYSTEM PENENTUAN PEGAWAI TERBAIK DENGAN METODE SAW(STUDI KASUS UNIVERSITAS BANTEN JAYA) - Indra Gunawan; Sutanto Sutanto; Irma Yunita (Teknik Informatika Fakultas Ilmu Komputer, 2018)
ABSTRACT Banten Jaya University is a private university in Serang city of Banten province. The increasing number of employees the diversity of employees is also increasingly complex so it is difficult to choose the best employees. Therefore, the need for a decision support system, so that it can shorten the selection time and improve the quality in determining the best employees. The best employee decision support system uses SAW (simple additive weighting) method based on predetermined criteria and weight. SAW (simple additive weighting) method is chosen because it is able to select the best alternative from a number of alternatives. This research is done by finding the weight on each attribute, then done ranking to determine the best employees.